ACHIEVING A SUSTAINABLE CITY IMAGE IN TERMS OF TWENTY-FOUR HOUR CITY PRINCIPLES: CASE OF THE KEMERALTI BAZAAR OF IZMIR, TURKEY - AVCI, Ali Berkay; BEYHAN, Ş. Gülin (MATTER: International Journal of Science and Technology, 2017)
Izmir is the 3rd largest and considered as the most livable city of the Turkey. In contrast with this livable city image, the center of Izmir turns into a deserted area after 19:00 pm, while it is crowded until that time. In order to achieve the sustainability of the livable city image of Izmir, it is prior to solve the problem of day and night usage disequilibrium of the city center. Present study focuses on the area of Kemeralti Bazaar, which is the historical center of Izmir. The purpose of the study is assessing the viability of the Twenty Four Hour City principles, that several cities in United Kingdom applied, as a solution for the day and night usage disequilibrium of the Kemeralti Bazaar. On account of this purpose the Twenty Four Hour City principles, which are licensing issues, retail working time, supporting restaurants and cafés, street lighting, mixed use space organization, city activities and public transportation, are introduced and their applicability for the sample area is evaluated. The method of the research comprises the pedestrian density data, on-site photography and land use diagrams in order to monitor the evaluation of the Twenty Four Hour City principles. The research showed that the area lacks the majority of the principles, which should be adopted to sustain the livable city image of Izmir and proper solutions for the problem are proposed in the conclusion.